SIMULATION OF PROTECTION OF THE AIR ENVIRONMENT FROM POLLUTION BY AMMONIA WITH LIQUID CURTAINS - Biliaiev, M. M.; Koptilaia, O. V. (Science and Transport Progress, 2003)
A computer model to simulate the ammonia cloud concentration reduction with sprinklers which used water or acid was developed. The model is based on 3D equation of admixture transfer written both for ammonia and neutralizator. The results of numerical experiment are presented.